Laser Retinotomy with “Ultra Q Reflex” System for the Prevention of Rhegmatogenous Retinal Detachment due to the Peripheral Horseshoe Tears - A. V. Doga (Oftalʹmologiâ, 2018)
Purpose. To evaluate laser retinotomy efficacy in the retinal detachment (RD) due horseshoe tear prevention. Patients and methods. 57 eyes of 54 patients with subclinical retinal detachment due to the peripheral horseshoe retinal tear were enrolled. 26 eyes of 25 patients of main group undergone combined laser technology included a barrier retinal photocoagulation of the local detachment zone, accompanied with deffered Nd:YAG laser retinotomy. The barrier retinal photocoagulation alone was performed on 31 eyes of 29 patients in control group to compare postoperation results. The assessment of the peripheral vitreoretinal interface was carried out by fundus ultrasound scanning, multispectral scanning laser imaging and spectral optical coherence tomography. The efficacy of the laser treatment was estimated by local retinal detachment height and area changes, while the safety was estimated by intra- and post-op complications rate. All patients were examined at the baseline, 1 week, 1, 3, 6 and 12 month follow-up. Results. Both main and control groups undergone barrier laser photocoagulation with complete round demarcation of subclinical local retinal detachment. All twenty five patients of main group achieved successful laser resection of retinal horseshore flap without any evidence of clinically significant complications. YAG-laser retinotomy in patients with retinal horseshoe tear resulted in decreased values of local retinal detachment height and area (in 40 and 38% respectively, p < 0.05). At the 12-month follow-up full retinal adhesion has been achieved in 15 eyes (58%), while partial adhesion has been observed in 7 eyes (27%). Obtained data were significantly lower compared with control group where some sings of retinal detachment progression were appeared (in 11 and 4% respectively, p > 0.05). No evidence of clinically significant complications after laser treatment has beenrevealed. Conclusions. The obtained data have demonstrated the efficacy and the safety of laser retinotomy in traction component reducing and consequent risk of retinal detachment minimising.